Retro fashion is centre stage. - Elliott, Giles (Bookseller, 2005)
In this article, the author comments on the present scenario of the nature of television programmes, films and books. He says that a visitor from another planet could be forgiven for expressing confusion over which decade he has landed in. With the television serial "Doctor Who" back on television screens and films of "The Hitchhiker's Guide to the Galaxy" and a new "Star Wars" episode looming over the cultural landscape, the next generation is absorbing the same influences as its parents. Wayne Gould's book of the numerical brainteaser, "The Times Su Doku," passed the 50,000 sales landmarks last week, and a second and third book of the puzzle will hit the shops in June and September respectively.